Engineering the expression of plant secondary metabolites-genistein and scutellarin through an efficient transient production platform in Nicotiana benthamiana L. - Yao, Xinghao; Wuzhang, Kuanyu; Peng, Bowen; Chen, Tiantian; Zhang, Yaojie; Liu, Hang; Li, Ling; Fu, Xueqing; Tang, Kexuan (Frontiers in Plant Science, 2022)
Plant natural products (PNPs) are active substances indispensable to human health with a wide range of medical and commercial applications. However, excessive population growth, overexploitation of natural resources, and expensive total chemical synthesis have led to recurrent supply shortages. Despite the fact that the microbial production platform solved these challenges, the platform still has drawbacks such as environmental pollution, high costs, and non-green production. In this study, an efficient platform for the production of PNPs based on the transient expression system of Nicotiana benthamiana L. combined with synthetic biology strategies was developed. Subsequently, the feasibility of the platform was verified by a simple “test unit”. This platform was used to synthesize two high-value PNPs: genistein (5.51 nmol g-1 FW) and scutellarin (11.35 nmol g-1 FW). Importantly, this is the first report on the synthesis of scutellarin in heterologous plants. The platform presented here will possibly be adopted for the heterologous production of genistein and scutellarin in tobacco plants as a novel and sustainable production strategy.